The nuts and bolts of the Haloferax CRISPR-Cas system I-B. Issue 4 (3rd April 2019) - Maier, Lisa-Katharina; Stachler, Aris-Edda; Brendel, Jutta; Stoll, Britta; Fischer, Susan; Haas, Karina A.; Schwarz, Thandi S.; Alkhnbashi, Omer S.; Sharma, Kundan; Urlaub, Henning; Backofen, Rolf; Gophna, Uri; et al.
ABSTRACT: Invading genetic elements pose a constant threat to prokaryotic survival, requiring an effective defence. Eleven years ago, the arsenal of known defence mechanisms was expanded by the discovery of the CRISPR-Cas system. Although CRISPR-Cas is present in the majority of archaea, research often focuses on bacterial models. Here, we provide a perspective based on insights gained studying CRISPR-Cas system I-B of the archaeon Haloferax volcanii . The system relies on more than 50 different crRNAs, whose stability and maintenance critically depend on the proteins Cas5 and Cas7, which bind the crRNA and form the Cascade complex. The interference machinery requires a seed sequence and can interact with multiple PAM sequences. H. volcanii stands out as the first example of an organism that can tolerate autoimmunity via the CRISPR-Cas system while maintaining a constitutively active system. In addition, the H. volcanii system was successfully developed into a tool for gene regulation.